Mensuração do desempenho estratégico no terceiro setor: o caso AMIC - Daradda, Lidiane Fernanda Rocha (2018)
The theme of this study refers to the use of the Strategic Performance Measurement System (SPMS) in organizations of the third sector, which have required performance mechanisms that apply to the management. Therefore, this research aimed to investigate how the Strategic Performance Measurement System can contribute to strategic planning in the third sector by means of performance indicators, justifying the application of SPMS in this segment that is differentiated and poorly explored. The theoretical reference was based on the Third Sector, Strategic Planning, Strategic Performance Measurement System and Previous Studies. For this purpose, a unique case study and action research with a qualitative focus were performed at AMIC. Data collection consisted of a focus group, questionnaires, documents, organizational records and participant observation, using the case study´s protocol and triangulation of research sources. The results confirmed the research propositions and the findings of the literature, and it was verified that the strategic planning allows the use of the measurement system in the organizations of the third sector through the elaboration of the SWOT Analysis and action plan; the evaluation of strategy implementation contributes to the performance of third sector organizations through the control, monitoring, identified gaps and positive influence on performance; and the elaboration of the own measurement model uses financial and non-financial indicators for the management in the third sector based on strategic direction. Thus, as result of the intervention, the management of the strategic actions was achieved, the implementation of the strategy generated benefits to the performance and the composition of a coherent set of performance measures were obtained. The main contributions show that the SPMS can be used in nonprofit organizations, in addition to those that aim for profit and make use of it, as well as contribute to the theoretical gap on appropriated performance measures to the third sector.